Mamasa-Kristen dan Kematian Anggota Keluarganya: Dialog yang Memperkaya antara 1 Tesalonika 4:14 dan Aluk Toyolo - Pelita Hati Surbakti; Rahyuni Daud Pori; Ekavian Sabaritno (Indonesian Journal of Theology, 2022)
The death of a family member often leaves deep sorrow. Because of that, in various cultures, there are mechanisms of consolation as also found in Aluk Toyolo. However, these mechanisms find occasional opposition within Christianity when seen as inconsistent with the teachings of the Bible. A church may even impose sanctions on congregants who continue to observe them. Such a situation presents an obvious dilemma for those abiding by two traditions or two texts, namely ancestral culture and Christian tradition. Known for their heritage of distinct death rites, Mamasa-Christians experience this very dilemma. Although the Mamasa Toraja Church (GTM) at the synod level has adopted a number of prohibitions, some of the prohibited rites are still practiced openly—a dilemma experienced by congregants and church, alike. So, what can be done to minimize this dilemma? This article proposes a dialogue in the realm of two texts hermeneutics called Cross-Textual Hermeneutics. From this dialogue, a number of points of contact can be found between the notion of death in the Mamasa ancestral culture and the concept of death in the writing of Paul the Apostle. While differences between the two traditions exist, there are also enriching differences to be found. Through such a dialogue, the understanding of the death in 1 Thessalonians 4:14 can be enriched by means of considering the death rite in Aluk Toyolo.